Design and Control of a Hydraulic Hexapod Robot with a Two-Stage Supply Pressure Hydraulic System - Ziqi Liu; Bo Jin; Junkui Dong; Shuo Zhai; Xuan Tang (Machines, 2022)
This paper focuses on the system design and control strategies of a hydraulic hexapod robot (HHR) ZJUHEX01 with a two-stage supply pressure hydraulic system (TSS). Firstly, a brief introduction is given, including the mechanical structure, the onboard hydraulic system, and the control system architecture. Secondly, the kinematics model and hydraulic system model are built in preparation for the controller design. Then a sliding mode repetitive controller (SMRC) for the separate meter in and separate meter out (SMISMO) hydraulic system is proposed, as well as the valve configuration, to help HHR get better control performance and smaller tracking errors. Furthermore, a high order sliding mode differentiator (HOSMD) is developed to obtain the joint angular velocity and acceleration. Finally, the ADAMS and MATLAB/Simulink co-simulation model is established to verify the effectiveness of the control strategy. Also, the energy consumption of TSS is compared with that of one-stage supply pressure hydraulic system (OSS) to show a great energy-saving effect of 51.94%.